Drawing Electoral Districts to Promote Minority Representation. Issue 3 (3rd July 2022) - Handley, Lisa
ABSTRACT: The conventional wisdom that List PR is the best electoral system for ensuring the inclusion of racial, ethnic or other minorities in parliament is not necessarily true if the minority group has not established its own political party. An electoral system that includes single-member or small multimember districts offers the same avenues for minority representation under this condition as a List PR system, but presents an additional possibility as well: electoral districts can be configured specifically to promote or guarantee the election of minority representatives. This descriptive comparative study provides a conceptual framework for organising the approaches districted systems have adopted and discusses the implications of these approaches for the inclusion of minorities in parliament and the accountability of these representatives to the minority community they are intended to represent. While restricting the candidates who can compete in a district to minority candidates guarantees descriptive representation, restricting the voters, either by drawing districts so that minorities make up a majority of the voters or through communal voter lists that permit only members of the minority group to vote for the district representative, may be better for enhancing substantive representation.